Mathematical modelling of a hydraulic servomechanism - Sugumaran Jeganathan. (2010)
Hydraulic servo systems are widely used in industry for motion control. The effects of varying the diameter and length of pipelines on the response and stability of an electrohydraulic system was investigated by mathematically modelling it using fluid mechanics and feedback control theroy.